Arvenses Cordia lutea y Baccharis conferta con ensilaje de maíz como alternativa de alimentación para terneros en dos etapas de levante - Marcillo Molina, Hermes Tobías (2023)
The present investigation was based on the use of weeds in combination with corn silage as an alternative feeding in calves. It was required to estimate the nutritional value of weeds: Muyuyo (Coria lutea) (T1 and T3) and Wild broom (Baccharis conferta) (T2 and T4) supplied to calves and at ages of 3 to 4 months (T1 and T2). and 4 to 5 months (T3 and T4) in relation to variables: daily weight gain (GPD), feed conversion index (ICA), a process that allowed the analysis of the economic impact of the use of weeds. The study applied a DCA that, based on the characterization of the weeds, the mountain broom presented a protein content of 5,84%; 28,38% dry matter and 9,4% crude fiber. Muyuyo presented a protein of 7,27%; dry matter of 30,51% and crude fiber of 9,4%. The application of these weeds presented a p-value less than 0,05 in the use of Coria lutea, which resulted in an increase in weight in T3 from 144,52 (S0) to 183,50 kg (S8) and in T1 from 137,07 (S0) to 159,32 kg (S8); with total GP (8 weeks) in T1 of 22,25 kg and in T3 of 38,99 kg. It is concluded that this type of weed presented a greater economic benefit when comparing the increase in weight obtained with the feeding types Coria lutea (0,40 and 0,70 kg) and Baccharis conferta (0,30 and 0,24 kg).